2006
DOI: 10.1124/mol.106.030684
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Factor-κB and Protein Kinase C Signaling in the Expression of the Kinin B1Receptor in Human Vascular Smooth Muscle Cells

Abstract: Kinin B 1 receptor expression was characterized in human umbilical artery smooth muscle cells to further elucidate the function and specificity of three previously proposed pathways [nuclear factor-B (NF-B), protein kinase C, and agonist autoregulation] that regulate this inducible G protein-coupled receptor. Radioligand binding assays, real-time reverser transcription/polymerase chain reaction with an optional actinomycin D treatment period, and NF-B immunofluorescence were primarily employed in these primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 37 publications
1
40
2
Order By: Relevance
“…The cells were washed twice with the binding medium and filled with 0.5 ml of prewarmed (37°C) binding medium. The binding medium was serum-free culture Medium 199 (Invitrogen) supplemented with 0.1% bovine serum albumin and sodium azide [0.02% (w/v)] for the peptide radioligand of the B 1 receptor only; 1 M amastatin, 1 M captopril, and 1 M phosphoramidon (Sigma-Aldrich) were added to the binding medium (as in our previous reports; Sabourin et al, 2002;Moreau et al, 2007). The experiments dealt with the effect of cell coincubation of the radioligand at a fixed concentration (1 nM) with a panel of unlabeled drugs.…”
Section: Drugs Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were washed twice with the binding medium and filled with 0.5 ml of prewarmed (37°C) binding medium. The binding medium was serum-free culture Medium 199 (Invitrogen) supplemented with 0.1% bovine serum albumin and sodium azide [0.02% (w/v)] for the peptide radioligand of the B 1 receptor only; 1 M amastatin, 1 M captopril, and 1 M phosphoramidon (Sigma-Aldrich) were added to the binding medium (as in our previous reports; Sabourin et al, 2002;Moreau et al, 2007). The experiments dealt with the effect of cell coincubation of the radioligand at a fixed concentration (1 nM) with a panel of unlabeled drugs.…”
Section: Drugs Andmentioning
confidence: 99%
“…The institutional research ethics board approved the anonymous use of human umbilical cord segments obtained after elective cesarean section deliveries. Primary cultures of human umbilical artery smooth muscle cells, which express endogenous kinin B 1 receptors (Morissette et al, 2006;Moreau et al, 2007), were obtained and propagated as described. To quantify the calcium mobilization induced or influenced by several B 1 receptor ligands in naturally expressed receptors of human origin, Fura-2 fluorometry (Invitrogen, Carlsbad, CA) was applied to the smooth muscle cells maintained in serum-containing medium, detached using trypsin-ethylenediamine tetraacetic acid, suspended in complete culture medium containing fetal bovine serum (to neutralize the trypsin), counted, centrifuged for 5 min at 1100 rpm at room temperature, and resuspended in Hanks' balanced salt solution (1ϫ, pH 7.4, prepared from 10ϫ concentrate; Wisent Canadian Laboratories, St. Bruno, QC, Canada) with 10 mM HEPES and 1.6 mM CaCl 2 .…”
Section: Drugs Andmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the localization of ACE in freshly isolated human umbilical blood vessels, immunostaining was applied to paraffin section of the vein and artery using the anti-ACE The translocation of NFmaintained in their regular culture medium 60-90 min after drug treatments using immunofluorescence as described [22]. …”
Section: Microscopymentioning
confidence: 99%
“…Data obtained previously have demonstrated that NF-κB signaling plays an important role in the process up-regulation of the bradykinin B 1 receptor (Moreau et al, 2007;Ni et al, 1998;Sabourin et al, 2002;Schanstra et al, 1998). Others have also shown that the NF-κB pathway is important for inflammatory cytokine enhanced expression of bradyinin B 1 and B 2 receptors in osteoblasts and fibroblasts (Brechter et al, 2008) ; TPCA-1 is a highly selective IκB kinase 2 inhibitor, the results from 57 assays gave a mean IC 50 = 17.9 nM on IKK-2 and has 22-fold selectivity over IKK-1 (Podolin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%